A Multidisciplinary Team Guided Approach to the Management of cT3 Laryngeal Cancer: A Retrospective Analysis of 104 Cases - Marchi, Filippo (Cancers (Basel), 2019)
The optimal treatment for T3 laryngeal carcinoma (LC) is still a matter of debate. Different therapeutic options are available: Transoral laser microsurgery (TLM), open partial horizontal laryngectomies (OPHLs), total laryngectomy (TL), and organ preservation protocols (radiation therapy (RT) or chemo-radiation (CRT)). This study aimed to retrospectively evaluate oncologic outcomes of 104 T3 LCs treated by surgery or non-surgical approaches from January 2011 to December 2016 at a single academic tertiary referral center. Each case was evaluated by a multidisciplinary team (MDT) devoted to the management of head and neck cancers. We divided the cohort into two subgroups: Group A, surgical treatment (TLM, OPHLs, TL) and Group B, non-surgical treatment (RT, CRT). For the entire cohort, two- and five-year overall survival (OS) rates were 83% and 56%, respectively. The two- and five-year disease-free survival (DFS) rates were 75% and 65%, and disease-specific survival rates were 93% and 70%, respectively. The N category was a significant independent prognosticator for OS (p = 0.02), whereas Group B was significantly and independently associated with DFS (HR 4.10, p = 0.006). Analyzing laryngo-esophageal dysfunction-free survival as an outcome, it was found that this was significantly lower in higher N categories (p = 0.04) and in cases that underwent non-surgical treatments (p = 0.002). Optimization of oncologic outcomes in T3 LCs may be obtained only by a comprehensive MDT approach, considering that different treatment options have heterogenous toxicity profiles and indications.